The Seventh Five Year Plan 1985-90 Volume II Sectoral Programmes of Development - Planning Commission, Government of India (Planning Commission, Government of India, 1985)
Approach and Major Thrusts in the Seventh Plan 1.1 Agriculture occupies a key position in the Indian economy because of its contribution to overall economic growth through supplies of food, raw materials and exports. It is a source of livelihood for a majority of the population and provides a large market for non-agricultural goods and services.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Seventh Five Year Plan- Programmes of Development